MackTuesday wrote:Okay, here we go again:

H = (1/g - 1/z) / (g - 1/z)

= (1 - g/z) / (g² - g/z)

Okay, clearly I just don't know what I'm doing. Because the damn magnitude response for the above is 1/g, not 1. So I was right in the first place:

- Code: Select all
`H = (1 - g/z) / (g - 1/z)`

Again setting z = exp(-iφ) and H = -1:

- Code: Select all
`(1 - g∙exp(-iφ)) / (g - exp(-iφ)) = -1`

1 - g∙exp(-iφ) = -g + exp(-iφ)

g + 1 = (g + 1)∙exp(-iφ)

exp(-iφ) = 1

φ = 0

This is true no matter what g is. If you're getting phase inversion anywhere other than zero frequency, there's probably something wrong with your implementation. There. I'm done. Finished. Finito. Complete. No more. Goodbye.